Use of an insulated tip knife in the management of a common foreign body in a child - Sanjay Rajput; Pratin Bhatt; Vatsal Bachkaniwala; Chaiti Gandhi; Rushi Pipavat; Varun Tadkalkar; Ravi Bokarvadia (Society of Gastrointestinal Intervention, 2022)
A 2-year-old child presented with button battery (BB) ingestion that had taken place 5 months previously. The BB was impacted within the post-cricoid esophageal wall without an obvious perforation or communication with the trachea. In view of the high surgical risk, we attempted to remove the BB endoscopically. BB removal was not possible with conventional devices due to the post-cricoid location and the invagination of the BB into the esophageal wall. We dissected the BB from the surrounding esophageal wall using an insulated tip (IT) knife and successfully extracted the BB. The use of an IT knife prevented inadvertent injury or perforation while dissecting the BB, and surgery was avoided.